Investigating candlestick patterns using fuzzy logic in the stock trading system - Mojtaba Sadeghi, Dariush Farid, Habibullah Ansari samanic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to design a stock market forecasting system based on candlestick patterns and use fuzzy logic to model market rules and candles. The present study investigates how to design an efficient trading algorithm using trading information analysis and signaling methods and combining them with the capabilities of fuzzy logic that have already been developed. The short- and medium-term benefits of the proposed method are proven in different markets. Furthermore, this study enables investors to use specialized knowledge so that they can invest more confidently. In this study, fuzzy logic is used to implement trading systems based on candlestick patterns. The implemented method achieved profitability and lower risk for two different markets without retraining the system and even for a different testing period.